Analysis of the Marketing Channel of Palasari Arabica Coffee Beans - Cecep Pardani; Waliah Mulyatillah; Luthfia Nur Fadhillah (International Journal of Quantitative Research and Modeling, 2023)
The coffee agro-industry has enough opportunities significant for conducted development where Thing could see from amount starting request increase. Ground coffee is one of the results of processing from coffee beans that have prospects as well as good market opportunities. This study aims to determine: Arabica coffee bean marketing channels in Giri Mekar Village, Cilengkrang District, Bandung Regency; The amount of Arabica coffee bean marketing margin at the level of Arabica coffee marketing agency in Giri Mekar Village, Cilengkrang District, Bandung Regency; The costs and benefits of Arabica coffee marketing in Giri Mekar Village, Cilengkrang District, Bandung Regency; Farmer's Share Arabica coffee in Giri Mekar Village, Cilengkrang District, Bandung Regency. The type of research used is a survey. Respondents in this study were 10% of Arabica coffee farmers in Giri Mekar Village as many as 30 people, 1 person collecting traders, and 5 industrial consumers. The results of this study indicate that there is one marketing channel for robusta coffee beans in Giri Mekar Village, Cilengkrang District, Bandung Regency, namely farmers, collector traders, and industrial Consumers. The amount of marketing margin on the marketing channel is IDR 75,000 per kilogram. The amount of marketing costs in the marketing channel is IDR 46,500 per kilogram. The marketing profit on the marketing channel is IDR 29,500 per kilogram. Farmer's Share on the marketing channel is 16.67%